Pelatihan Sistem Informasi Keuangan Desa Sebagai Upaya Tertib Administrasi Desa Wisata Melung - Sholikhatin, Siti Alvi; Fatwa, Nu'maa Nabila; Zaman, Khayatuz (Jurnal Pengabdian Masyarakat (ABDIRA), 2024)
The village financial information system provides convenience for village officials in managing village finances in the context of orderly administration with the aim of successful village development. This training on the use of the financial information system aims to assist the community and village officials of Melung Village to be able to utilize the village financial website optimally. The training methods were seminars and workshops. Seminars were conducted to introduce the features of the website so that users were able to understand and use it as needed. The workshop was conducted to put into practice the information learned during the seminar. The main purpose of this training is as a community service activity in an effort to order administration and optimize village financial management for the welfare of the community. The result of the training activity is the implementation of automation of inputting income and expenses by village officials in village financial management as an effort to create transparency in reporting the use of village funds.